SECONDARY WAYS OF WORD-FORMATION (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This insightful article explores the nuanced realm of word formation by delving into both primary and secondary processes. It effectively communicates the significance of secondary methods, such as blending, acronyms, backformation, and others, in enhancing language flexibility and adaptability. The examples provided illustrate how these processes capture evolving societal, cultural, and technological dynamics. Furthermore, the additional information highlights the crucial role of external influences, including culture, technology, globalization, slang, and specialized fields, in shaping linguistic landscapes. The article successfully portrays language as a living entity, constantly evolving to mirror the multifaceted tapestry of human communication. Overall, this comprehensive exploration offers valuable insights into the intricate mechanisms that drive language evolution, making it a insightful read for those interested in linguistics, language development, and the dynamic interplay between words and society.